Speaking Up and Being Heard: The Importance of Functional Communication and Discourse Principles in Aphasia Intervention - Armstrong, Elizabeth; Hersh, Deborah (Seminars in Speech and Language, 2024)
This article acknowledges Audrey Holland's influence on aphasiology as it specifically relates to the emergence of a strengths-based perspective on the everyday communication of people with aphasia. We explore a historical perspective, as well as current ways in which everyday communicative events are approached in both clinical and research practice. The term “functional communication” is synonymous with Audrey's work, with linguistically-based discourse analysis and therapy both viewed as natural companions and extensions of the concept within aphasiology. Audrey's focus on the interactional side of communication and psychosocial impacts of aphasia, as well as her expertise in analysis and measurement, contributed to the coalescing of impairment-based and social communication approaches, encompassing a true sense of humanity and connectedness. Her application of these in international contexts was also noteworthy. In this article, we hope to capture principles of aphasia management that underpin current clinical practice, and also move beyond the traditional clinic context to consider aphasia groups that have had such a key role in promoting successful social communication by and with people with aphasia. We suggest future directions to further promote the principles advocated by Audrey Holland in assisting people with aphasia to move forward with confidence with their conversation partners, friends, and communities.
Keywords: aphasia; functional communication; discourse; conversation; group therapy